2020
DOI: 10.2140/pjm.2020.305.153
|View full text |Cite
|
Sign up to set email alerts
|

Index estimates for free boundary constant mean curvature surfaces

Abstract: In this paper we consider compact constant mean curvature surfaces with boundary immersed in a mean convex body of the Euclidean space or in the unit sphere. We prove that the Morse index is bounded from below by a linear function of the genus and number of boundary components.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In particular, as a byproduct, they showed that the index of free boundary CMC surfaces in a mean convex domain of R 3 is bounded below by (2g − r − 4)/6 where g is the genus of the surface and r is the number of boundary components of the surface. This particular result was also obtained by Cavalcante-de Oliveira in [12]. Here we generalize these results to compact capillary surfaces.…”
Section: Introductionsupporting
confidence: 85%
“…In particular, as a byproduct, they showed that the index of free boundary CMC surfaces in a mean convex domain of R 3 is bounded below by (2g − r − 4)/6 where g is the genus of the surface and r is the number of boundary components of the surface. This particular result was also obtained by Cavalcante-de Oliveira in [12]. Here we generalize these results to compact capillary surfaces.…”
Section: Introductionsupporting
confidence: 85%
“…There are plenty of works on the index estimate for closed minimal hypersurfaces or minimal hypersurfaces with free boundary, see for example, Ros [20], Savo [25] and Ambrozio-Carlotto-Sharp [2,3]. See also [19,11,12] for index estimate for CMC surfaces with free boundary, which is related to type-I partitioning problem. The technique in [19,11,12] for non-minimal CMC case only applies for two dimension.…”
Section: Introductionmentioning
confidence: 99%
“…See also [19,11,12] for index estimate for CMC surfaces with free boundary, which is related to type-I partitioning problem. The technique in [19,11,12] for non-minimal CMC case only applies for two dimension.…”
Section: Introductionmentioning
confidence: 99%
“…In the free boundary hypersurface case, Ambrozio, Carlotto and Sharp [3] and Sargent [11] explored the same strategy and also obtain interesting comparison results. In codimension one case, we also point out the paper [1, 4], where the authors were able to adapt the main ideas above cited to the free boundary constant mean curvature setting.…”
Section: Introductionmentioning
confidence: 95%